Praktik On The Job Training (OJT) II Pelatihan Calon Pengawas Madrasah - Surip Riyadi (An-Nidzam : Jurnal Manajemen Pendidikan dan Studi Islam, 2022)
On The Job Training is one of the best methods for providing high skills or skills to employees because this method is planned, organized and carried out in the workplace and employees are trained on how they carry out their job duties. This article aims to (1) provide an overview of the implementation of each item of activity which is the main task of prospective school/madrasah supervisors along with various supporting and inhibiting factors in the implementation of each item of school/madrasah supervision; and (2) Provide an overview of the condition of the assisted school/madrasah based on the results of an assessment conducted by prospective school/madrasah supervisors. Based on the results and discussion of the practice of On The Job Training (OJT) II, the following conclusions can be drawn: (1) The understanding of prospective Madrasah supervisors on supervision regulations is very important so that prospective supervisors are not mistaken in making policies related to the supervisory program; and (2) To carry out the supervision program, it is necessary to build good synergy between teachers, madrasah heads, supervisors, and related agencies so that the supervision program is maximally successful.